Development of Kids Multimedia Interactive Songs (K-MIS) / Siti Husna Mohd Yusuff - Mohd Yusuff, Siti Husna (2004)
Multimedia presentation is widely accepted as a successful learning aid that proved to enhance the interest and the skill of the targeted audience. With the interactive features found in the presentation, the multimedia learning approach has widely been accepted all around the world. Learning songs also are now available in the multimedia presentation. As for children songs, the nursery song is also available in the multimedia compact disc format. Kids Multimedia Interactive Songs or K-MIS is develop specifically for children from age 4 years to 6 years. The content of the courseware is Malay children songs. In developing the courseware, methodology that consists of planning, analysis, design, development and refinement phase is used. The data is collected through observation on several nursery center and interviews with one of the nursery center teacher. K-MIS courseware is develop in an interactive form that allows the children to participate in the learning process. The user can decide what type of song and stories they want. This courseware emphasize on the usage of Malay language as a delivering platform in order to enhance the skill of mastering our national language and to popularize again our tradition culture in term of Malay children sons.